About the problems of business activity of young people taking into account the factors of the economic environment - R. M. Ustaev; O. A. Boris; M. N. Ustaeva; A. E. Zhuravel (Вестник Северо-Кавказского федерального университета, 2022)
A systematic analysis of the state of youth entrepreneurship in Russia and the North Caucasus Federal District, the prospects for its development was carried out. The reasons that prevent graduates from deciding to open their own business are investigated, with an emphasis on the problems that have arisen in the context of pandemic restrictions. The importance of implementing measures aimed at restoring the growth rate of the Russian economy is shown. The main principles of policy in the field of regulation of youth business are identified, taking into account the digital economy and the coronavirus pandemic. For the effective implementation of the planned, it is necessary to significantly change the strategic approach to the system of youth entrepreneurship and measures to stimulate it, move from targeted selective assistance to long-term support measures for businesses created by young people and its development at each stage of the life cycle, taking into account the sectoral characteristics of business in various industries economy.